Liturgy and chant in a twelfth-century Exeter missal. Issue 2 (October 2019) - MANNION, ANNE
Abstract: Exeter Cathedral Library and Archives MS 3515 (hereafter EXcl 3515), a notated missal located in Exeter Cathedral, has to date received very little scholarly attention. This neglect may be due to the absence of a liturgical kalendar and evidence of local saints in the Sanctorale . Its assignment to the thirteenth century with a generic English origin suggests that critical questions concerning provenance and dating have been overlooked. The source itself comprises four disparate sections assembled so as to create a complete liturgical cycle. Yet the parts are not as separate as hitherto believed. A comparative investigation reveals not only an Exeter provenance and a twelfth-century dating, but also a new witness to the St Denis/Corbie tradition. Research also reveals unexpected threads of liturgical continuity with the Anglo-Saxon past. As a complete pre-Sarum source of Mass prayers, chants and readings, EXcl 3515 offers a useful lens with which to view a transitional period in the development of a medieval secular liturgy in England. (By contrast, the three dominant cathedrals – Salisbury, York and Hereford – all lack notated chant sources from this period.) EXcl 3515 adds not only significant new data to the current information on secular liturgies, but also challenges accepted theories on the shaping of a distinctive English Use in southwest England.